Improving educational quality with interactive radio instruction : a toolkit for policymakers and planners - Anzalone, Stephen; Bosch, Andrea (Africa Region Human Development Working Papers Series No.52, 2005)
This toolkit offers a timely compilation and analysis of recent experience of interactive radio instruction (IRI) in Africa and elsewhere. It explains the IRI concept. It guides the reader through the process of determining when IRI might be appropriate in a given context, and it describes the steps in setting up an IRI program. The authors emphasize the critical factors for success, including appropriate policy frameworks as well as planning for the necessary investment and sustainability. The report is organized as follows: Chapter 1 generally describes the IRI methodology and discusses the effectiveness, scale, and sustainability of the IRI approach. Chapter 2 then outlines steps for assessing the potential and appropriateness of IRI for improving educational quality in primary school classrooms in a given country, and chapter 3 leads the reader through a guided decision-making process for identifying the issues involved in applying the IRI methodology in particular country contexts. Two appendixes give summary data and illustrate, through brief vignettes, how IRI programs have worked in Sub-Saharan African countries. The Resources section contains further useful information, much of it available online.
Keywords: Commitment; ___working_potential_duplicate; broadcasting; cost

Improving Educational Quality through Interactive Radio Instruction - World Bank (2005)